1987
DOI: 10.1246/cl.1987.763
|View full text |Cite
|
Sign up to set email alerts
|

The pH-Sensitive Conversion of Molecular Aggregates of Rhamnolipid Biosurfactant

Abstract: Rhamnolipid B and its precursor A, both microbial and membranous constituent, reversibly changed morphologies of their molecular aggregates from vesicles under acidic conditions, to lamella, lipid particles, and finally to micelles under weakly acidic conditions within a narrow pH range of about 5–7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 17 publications
10
79
0
2
Order By: Relevance
“…However, at pH 4, the carboxyl groups do not carry any charge. Ishigami et al (1987) described similar behaviour. Sánchez et al (2007) found a CMC value of 0.110 mM at pH 7.4 and 0.010 mM at pH 4 with purified dirhamnolipids.…”
Section: Ph Behaviourmentioning
confidence: 63%
See 1 more Smart Citation
“…However, at pH 4, the carboxyl groups do not carry any charge. Ishigami et al (1987) described similar behaviour. Sánchez et al (2007) found a CMC value of 0.110 mM at pH 7.4 and 0.010 mM at pH 4 with purified dirhamnolipids.…”
Section: Ph Behaviourmentioning
confidence: 63%
“…In aqueous media, biosurfactants, like surfactants, have different types of aggregates depending on their structure (Sánchez et al, 2007;Imura et al, 2007). Furthermore, it has been reported that biosurfactant aggregation properties depend on the pH of the medium (Israelachvili et al, 1976;Ishigami et al, 1987Ishigami et al, , 1993Champion et al, 1995).…”
Section: Basic Propertiesmentioning
confidence: 99%
“…The data was then used to estimate the critical micelle concentration (CMC). The rhamnolipid solutions were prepared in phosphate buffer to control pH which is known to have a significant influence on the morphology of the surfactant aggregates [28,29]. Micelles are the predominant species at a pH greater than 6.8 [28].…”
Section: Interfacial Tension Measurementsmentioning
confidence: 99%
“…The rhamnolipid solutions were prepared in phosphate buffer to control pH which is known to have a significant influence on the morphology of the surfactant aggregates [28,29]. Micelles are the predominant species at a pH greater than 6.8 [28]. Further, Zhang and Miller [9] observed a maximum reduction in surface tension of rhamnolipid solutions at pH 7.…”
Section: Interfacial Tension Measurementsmentioning
confidence: 99%
“…This phenomenon may be attributed to a gradual growth of ionic micelle with the increase of GL concentration owing to the bulky molecular structure. Rhamnolipid A and B also showed a similar behavior to GL in the gradual association because of the similarity of their chemical structures,both being liposaccharides with c~,~-hydrophilic moieties(Ishigami et al 1987). Surface and interracial tensions of GL in PBS buffer (pH 7.35) are summarized inTable l. GL exhibits a high surface activity in spite of the molecular bulkiness.…”
mentioning
confidence: 89%